Capturing a novel metastable polymorph of the anticancer drug gefitinib - Thorat, Shridhar H.; Patwadkar, Manjusha V.; Gonnade, Rajesh G.; Vaidhyanathan, R. (CrystEngComm, 2014)
Gefitinib, a life-extending anticancer drug, exhibits solvent-mediated conformational polymorphism to yield stable (form I) and novel metastable (form II) polymorphs. Crystal structure analysis revealed 3D isostructurality in the molecular organization of the polymorphs, and the metastable polymorph undergoes a crystal-to-crystal thermal phase transition to the stable polymorph.

Drug-drug molecular salt hydrate of an anticancer drug gefitinib and a loop diuretic drug furosemide: an alternative for multidrug treatment - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Patwadkar, Manjusha V.; Badiger, Manohar V.; Gonnade, Rajesh G. (Journal of Pharmaceutical Sciences, 2015)
A 1:1 monohydrate salt containing gefitinib, an orally administrated chemotherapy treatment for lung and breast cancers and furosemide, a loop diuretic drug, commonly used in the treatment of hypertension and edema, has been prepared. The molecular salt crystallized in triclinic P-1 space group. The CO bond lengths (similar to 1.26 angstrom) in the COOH group show that proton transfer has occurred from furosemide to morpholine moiety of the gefitinib suggesting cocrystal to be ionic. The morpholine moiety of the gefitinib showed significant conformational change because of its involvement in conformation dictating the strong N-H center dot center dot center dot O hydrogen bonding interaction. The strong hydrogen bonding interaction between gefitinib and furosemide places their benzene rings in stacking mode to facilitate the generation of pi-stack dimers. The neighboring dimers are bridged to each other via water molecule through N-H center dot center dot center dot O, C-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O interactions. The remarkable stability of the salt hydrate could be attributed to the strong hydrogen bonding interactions in the crystal structure. Interestingly, release of water from the lattice at 140 degrees C produced new anhydrous salt that has better solubility and dissolution rate than salt hydrate. The drug-drug molecular salt may have some bearing on the treatment of patient suffering from anticancer and hypertension. (C) 2015 Wiley Periodicals, Inc. and the American Pharmacists Association
Keywords: cancer chemotherapy; cocrystals; crystal engineering; crystal structure; dissolution rate; hydrate; phase transition; solubility; stability; thermal analysis

Efficient Ag-nanoparticle embedded semi-IPN hydrogel for catalytic applications - Patwadkar, Manjusha V.; Gopinath, Chinnakonda S.; Badiger, Manohar V. (RSC Advances, 2015)
Silver nanoparticle embedded semi-IPN hydrogels based on a combination of poly(acrylamide) and poly(aspartic acid) were synthesized. These semi-IPN hydrogel networks can potentially serve as micro or nano reactors for entrapment of metal nanoparticles. Current methodology allows us to entrap metal nanoparticles throughout hydrogel networks via poly(aspartic acid) chains which are dispersed homogeneously in the gel matrix. The Ag-NPs were characterized by UV-vis absorption spectroscopy, transmission electronic microscopy (TEM), X-ray diffraction (XRD) and energy dispersive X-ray analysis (EDAX). The Ag embedded hydrogels catalyze the reduction of 4-nitrophenol to 4-aminophenol in the presence of NaBH4 very efficiently at room temperature with good recyclability upto 3 cycles.

High-performance sultone-modified PVA/PAMPS semi-IPN hydrogels for proton exchange membranes - Patwadkar, Manjusha V.; Illathvalappil, Rajith; Torris, Arun; Francis, Sifa C.; Kurungot, Sreekumar; Badiger, Manohar V. (Journal of Applied Polymer Science, 2026)
Hydrogel membranes composed of poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS) and sultone-modified poly(vinyl alcohol) (PVA) were successfully synthesized and evaluated as promising proton-conducting materials. A key advantage involves the premodification of PVA with 1,3-propane sultone to introduce sulfonic acid groups, thereby imparting proton conductivity to the PVA backbone. This sultone-modified PVA was then physically entangled within a PAMPS cross-linked network to form novel semi-interpenetrating network (semi-IPN) hydrogels. This synergistic design leverages the excellent film-forming and mechanical properties of PVA with the high proton conductivity inherent to PAMPS. The synthesized membranes exhibited robust mechanical properties, with tensile strengths ranging from 5 to 30 MPa and percentage elongations between 200% and 400%, depending on their humidity content. These hydrogel membranes demonstrated proton conductivities ranging from 0.6 to 4.3 x 10-2 S cm-1. The activation energy for proton conduction was found to be as low as 3.5 kJ mol-1, significantly lower than that of the commercial benchmark membrane, Nafion 117 (12 kJ mol-1). These findings underscore the potential of these novel PAMPS/sultone-modified PVA semi-IPN hydrogel membranes for advanced fuel cell applications.
Keywords: batteries and fuel cells; functionalization of polymers; Gels; membranes; polyelectrolytes